CCNA security exam cram - Stewart, Eric L. (Exam cram., 2009)
In this book you'll learn how to: Build a secure network using security controls Secure network perimeters Implement secure management and harden routers Implement network security policies using Cisco IOS firewalls Understand cryptographic services Deploy IPsec virtual private networks (VPNs) Secure networks with Cisco IOS® IPS Protect switch infrastructures Secure endpoint devices, storage area networks (SANs), and voice networks WRITTEN BY A LEADING EXPERT: Eric Stewart is a self-employed network security contractor who finds his home in Ottawa, Canada. Eric has more than 20 years of experience in the information technology field, the last 12 years focusing primarily on Cisco® routers, switches, VPN concentrators, and security appliances. The majority of Eric's consulting work has been in the implementation of major security infrastructure initiatives and architectural reviews with the Canadian Federal Government. Eric is a certified Cisco instructor teaching Cisco CCNA, CCNP®, and CCSP® curriculum to students throughout North America and the world. CD Features MeasureUp Practice Questions! This book includes a CD-ROM that features: Practice exams with complete coverage of CCNA® Security exam topics Detailed explanations of correct and incorrect answers Multiple exam modes Flash Card format An electronic copy of the book informit.com/examcram ISBN-13: 978-0-7897-3800-4 ISBN-10: 0-7897-3800-7.